Quantitative interpretation of well logs for cases of low quality logs and limited measurement methods - CZOPEK, Barbara; NOWAK, Józef (Geology, Geophysics and Environment, 2011)
This paper presents a causal analysis of the most common errors occurring during recording and preliminary processing of well logs on both archival as well as current data obtained with Halliburton tools. The authors discuss the ways to identify and to correct these errors, under specific conditions. They present graphic examples of recording errors and the effects of their elimination. Examples of applying corrected standardized logs in petrophysical quantitative analysis involving determination of mineral composition, porosity and water saturation are provided by the authors. It is their opinion that the results of such analysis make it possible to generate reliable synthetic (theoretical) logs of density and interval transit time, which are useful input data in solving various geological problems related to hydrocarbon exploration, production and storage, to geothermal energy sources and many other issues.